Essays on board gender diversity and corporate governance - Coletta, Carolina (2024)
This thesis explores board gender diversity in Brazil and its relationship with two main aspects: corporate governance (CG) and firm value. In the first chapter, we present the evolution of women participation in Brazilian boards of directors from 2010 to 2020. Their presence is higher in low-corporate governance requirement listings. However, when we consider independent female directors, their presence is higher in high-CG listings. In chapter two, we investigate whether board gender diversity is determined by firm-level corporate governance (CG). Previous research has failed to control for CG level when analyzing board gender diversity and firm outcomes, such as firm value. We find that CG negatively predicts measures of overall, non-independent and family-related female directors. However, such relationships turn positive when considering female independent directors. Our results contribute to the importance of controlling for CG to obtain unbiased estimates on the relation between female directors and firm performance, as they are both determined by CG. Finally, the third chapter investigates whether board gender diversity predicts firm value in Brazil. Our results show that overall measures of female directors (FD) or independent FD do not predict firm value in Brazil. However, there is a negative relationship between non-independent FD and firm value, driven by female directors that are members of the controlling family.